Designing and Integrating Modern Data Centers. - Hunt, Andrew A. (Architectural Record, 2025)
The article focuses on the design, infrastructure, and technological advancements of modern data centers, which are increasingly vital for supporting AI and cloud services. It provides a historical overview of data center evolution, highlighting the transition from early mainframe environments to large-scale, hyperscale facilities that accommodate the growing demands of internet and cloud computing. Key topics include the shift from air-cooled to liquid-cooled systems, strategies for heat mitigation and reuse, and architectural solutions aimed at minimizing noise and visual impact. The article emphasizes the importance of understanding these developments to enhance performance, sustainability, and livability in digital infrastructure.